Effects of petroleum sludge ash in fly ash-based geopolymer mortar - Usman Kankia, M. (Elsevier Ltd, 2021)
Due to its encapsulation capacity and low carbon emission, geopolymer mortar is recognized as a possible substitute for Portland cement. This paper reports an experimental procedure of producing geopolymer mortar using petroleum sludge ash (PSA) and fly ash. Replacement levels of PSA were 0 â 20 by the weight of fly ash, 8 â 16 molarity of NaOH, 1.5 â 2.5 ratio of Na2SiO3 to NaOH were used. The 28 days compressive strength of geopolymer mortar made with 10 PSA was found to be the highest (31 MPa). Using variance analysis, the influence of NaOH concentration, the ratio of Na2SiO3 to NaOH, and PSA on the behavior of geopolymer mortars was acquired. The defined models were found to be significant for p-values < 5. The concentrations of the targeted heavy metals were found to be within the permissible level of USEPA. Â© 2020 Elsevier Ltd